Critical Thinking Skills Through Integration of Problem-Based Learning with Inquiry in Science Learning - Safitri, Dian; Rukman, Wira Yustika; Nurul Magfirah; Bachtiar, Suhaedir (Indonesian Journal of Science and Education, 2022)
This study aims to determine students' critical thinking skills through an inquiry learning model with problem based learning. This research is classroom action research. The subjects of the study were all class VIII students of SMP Negeri 2 Rumbia, totaling 2 groups with 15 students in one group in accordance with the limited face-to-face learning rules in the era of the covid 19 pandemic. The test instrument used was in the form of open questions (essay form) according to the grid. test. Critical thinking skills that are measured are identifying and formulating problems, giving arguments, making deductions, conducting inductions, evaluating, and deciding and carrying out actions. The results showed that the Problem Based Learning learning model with Inquiry was effectively used to improve students' critical thinking skills. Students' critical thinking skills have increased from cycle 1 to cycle 2 with an average pretest score of 50.25, while the posttest average score is 87.48. There was a significant increase in students' critical thinking skills in cycle 2 who were taught using the Problem Based Learning learning model with Inquiry, namely 37, 23